EPIDEMIOLOGY, CLINICAL CHARACTERISTICS, PREVENTION AND CONTROL OF CORONAVIRUS - A REVIEW - Devi, Shruthi; Priya, Jothi; Ganesh Mohanraj, Karthik (International Journal of Psychosocial Rehabilitation, 2020)
The world is in a big lockdown due to the coronavirus. It is caused by a novel virus , a modification of SARS-CoV-2, and is spread through human-to-human transmission, and as the days pass by, the death rate is increasing rapidly as people are not following the prevention protocol properly, and some are still not aware of the serious effects and preventive measures to be taken. It appeared just one month before the spring festival of China, and the massive population flow has brought great challenges for control and prevention of the disease. No specific therapeutic drug has been found for this disease. Hence, health education on knowledge for controlling the disease is important. So, this review focuses on decreasing the mortality rate and thereby helping people return to their normal life. The review was made by collecting information based on the keywords and important points in relation to the topic through search engines like PubMed and Google Scholar.The present study summarizes and gives an overview of COVID-19 that provides an insight to the people on this deadly disease and hence helps the people to stay safe.